Stereotypical Representation Of Professional Behavior Of Accountants In Cinematographic Technology Based On The Code Of Ethics Of The Accounting Profession - Kamil, Islamiah; Ghazy Arkan, Haidar; Fadjar Kurniawan, Donie (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the stereotypical representation of accountant professional behavior in cinematographic technology and how the stereotypical representation of accountant professional behavior is in accordance with or contrary to the code of ethics of the accounting profession. In the media of cinematography, accountants are often depicted with certain stereotypes that can affect the public's perception of the accounting profession. This study uses a qualitative method with content analysis from various movies and television series featuring accountant characters. Data was collected through literature review, observation, and interviews with experts in the field of accounting and cinematography. The results show that many of the accountant's representations in cinematography tend to focus on negative aspects such as dishonesty, boredom, and greed. These stereotypes often do not reflect the reality of the accounting profession governed by a strict code of ethics, including the principles of integrity, objectivity, and professionalism. This study emphasizes the importance of more accurate and balanced representation in the media to avoid public misconceptions about the accounting profession. Recommendations from the study include increased collaboration between the film industry and accountant professional organizations to ensure fairer and more educational representation. In addition, this research encourages filmmakers to better understand and respect the code of ethics of the accounting profession in their works.